Physiological and anthropometric correlates of tackling ability in rugby league players - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2009)
This study investigated the relationship between physiological and anthropometric qualities and tackling ability in rugby league players. Twelve rugby league players (mean ± SD age, 24.4 ± 3.5 years) underwent a standardized 1-on-1 tackling drill in a 10-m grid. Video footage was taken from the rear, side, and front of the defending player. Tackling proficiency was assessed using standardized technical criteria. In addition, all players underwent measurements of anthropometry (stature, body mass, sum of 7 skinfolds, arm, chest, waist, gluteal, thigh, and calf girths, and biepicondylar humerus and femur breadths), somatotype (endomorphy, mesomorphy, and ectomorphy), acceleration (5- and 10-m sprint), change-of-direction speed (modified 505 test), lower-body muscular power (vertical jump), and upper-body muscular power (overhead medicine ball throw). Differences in tackling ability and physiological and anthropometric qualities between the best (N = 6) and worst (N = 6) tacklers were compared using the Cohen effect size (ES) statistic. Eta coefficients (n) were used to determine the relationships among physiological and anthropometric qualities and tackling proficiency. Better tacklers were older (ES = 1.9), more experienced (ES = 1.0), shorter (ES = 1.2), lighter (ES = 2.3), and leaner (ES = 1.3) than players with poor tackling proficiency. Better tacklers also had greater levels of mesomorphy (ES = 0.3), acceleration (ES = 2.3), and change-of-direction speed (ES = 0.5) than poor tacklers. The strongest correlates of tackling ability were age (? = 0.70), skinfold thickness (? = -0.68), body mass (? = -0.72), waist girth (? = -0.79), gluteal girth (? = -0.74), and level of endomorphy (? = -0.65). These findings demonstrate that well-developed physiological and anthropometric qualities contribute to effective tackling ability in rugby league players.